Moving Beyond GDP: Cost Effectiveness of Cochlear Implantation and Deaf Education in Latin America. Issue 8 (September 2016) - Emmett, Susan D.; Tucci, Debara L.; Bento, Ricardo F.; Garcia, Juan M.; Juman, Solaiman; Chiossone-Kerdel, Juan A.; Liu, Ta J.; de Muñoz, Patricia Castellanos; Ullauri, Alejandra; Letort, Jose J.; Mansilla, Teresita; Urquijo, Diana P.; et al.
Abstract : Hypothesis: Cochlear implantation (CI) and deaf education are cost effective management strategies of childhood profound sensorineural hearing loss in Latin America. Background: CI has been widely established as cost effective in North America and Europe and is considered standard of care in those regions, yet cost effectiveness in other economic environments has not been explored. With 80% of the global hearing loss burden existing in low- and middle-income countries, developing cost effective management strategies in these settings is essential. This analysis represents the continuation of a global assessment of CI and deaf education cost effectiveness. Methods: Brazil, Colombia, Ecuador, Guatemala, Paraguay, Trinidad and Tobago, and Venezuela participated in the study. A Disability Adjusted Life Years model was applied with 3% discounting and 10-year length of analysis. Experts from each country supplied cost estimates from known costs and published data. Sensitivity analysis was performed to evaluate the effect of device cost, professional salaries, annual number of implants, and probability of device failure. Cost effectiveness was determined using the World Health Organization standard of cost effectiveness ratio/gross domestic product per capita (CER/GDP)<3. Results: Deaf education was very cost effective in all countries (CER/GDP 0.07–0.93). CI was cost effective in all countries (CER/GDP 0.69–2.96), with borderline cost effectiveness in the Guatemalan sensitivity analysis (Max CER/GDP 3.21). Conclusion: Both cochlear implantation and deaf education are widely cost effective in Latin America. In the lower-middle income economy of Guatemala, implant cost may have a larger impact. GDP is less influential in the middle- and high-income economies included in this study.